DEEP Study: does EQ‐5D‐5L measure the impacts of persistent oro‐facial pain?. (30th March 2015) - Durham, J.; Steele, J.G.; Breckons, M.; Story, W.; Vale, L.
Summary The EQ‐5D‐5L is a generic quality of life (QOL) measure widely used throughout the world, which has the advantage that it allows health‐state preferences to be elicited. The aim of this study was to examine whether: a) variation in the standardised reference period for EQ‐5D‐5L from 'today' to 'the last month' had a minimal clinically meaningful difference; (b) EQ‐5D‐5L had convergent validity with a multidimensional pain measure in quantifying the impacts of pain. As part of a larger study into the effectiveness and efficiency of care pathways for persistent orofacial pain (POFP) (http://research.ncl.ac.uk/deepstudy), participants with POFP (n = 100) completed two versions of the EQ‐5D‐5L at the same time with different reference periods ('today' vs. 'last month'). Participants also completed the first section of the West Haven–Yale Multidimensional Pain Inventory (v3) to assess convergent validity. Two‐tailed nonparametric inferential statistics, intra‐class correlation coefficients (ICC), and within‐subject change scores were used to compare the two EQ‐5D‐5L versions. Convergent validity was assessed using Spearman's rho correlation coefficients. Health‐state valuations were significantly different (P < 0·01), and there was good similarity between the two versions' ICC 0·86 (95% CI 0·79–0·91). The within‐subject mean change was 0·03 (95% CI 0·01–0·06). For convergent validity, all relationships were significant (P < 0·05) and in the expected directions. EQ‐5D‐5L demonstrates sufficient convergent validity to be used with POFP, and a change in the standard reference period may be unnecessary if a multidimensional pain measure is also used.